Historical essay about Ekaterinoslav school of histology. Part II: 1962-2000 - Marchenko, D. G.; Morozova, S. B.; Petruk, N. S.; Pototska, O. Yu.; Romanenko, L. A.; Stanishevska, N. V.; Sultanova, N. M.; Filimonova, L. A.; Khripkov, I. S.; Shevchenko, K. M.; Tverdokhlib, I. V. (Морфологія / Morphologia / Morfologìâ, 2017)
Further development of the Dnepropetrovsk histological school from 1962 to 1989 is associated with the name of Professor Vladimir Ivanovich Arkhipenko. Having performed under the guidance of Professor BV Alyoshin the thesis for a candidate's degree, V.I. Arhipenko devoted his further work to the study of the endocrine system, especially the thyroid gland.